Psychological Construction and Cultivation of New Entrepreneurs Using Industrial Cluster Theory and Multidimensional Structure Model - Fan, Huiling (Frontiers in Psychology, 2021)
This study aims to analyze the influencing factors and training plans of cultivating new entrepreneurs in the new era based on industrial cluster theory. First, the status of the research on the correlation between psychological characteristics and entrepreneurial performance of new entrepreneurs is reviewed. Second, 200 new entrepreneurs in the Xi’an City of Shaanxi Province are randomly selected as the research objects. An empirical model of the correlation between entrepreneurial psychological characteristics and entrepreneurial performance is innovatively proposed. Finally, the questionnaire data are analyzed by correlation analysis and SPSS 26.0 (Chicago) statistical analysis. The results show that most of the entrepreneurs are between 30 and 50 years old, with a larger number of mens, and most graduate from junior colleges. The gender and education level of the new entrepreneurs have a little impact on their entrepreneurial performance (P > 0.05), whereas their age has a significant impact on their entrepreneurial performance (P < 0.05). Moreover, there is a significant correlation between the psychological characteristics of the entrepreneur and the two dimensions of entrepreneurial performance (development and profitability) (P < 0.05). This shows that the key to cultivating new entrepreneurs is to develop their age and psychological characteristics, which can enhance the entrepreneurial ability of new entrepreneurs and provide a basis for cultivating multidimensional entrepreneurial talents in new enterprises.